2020
DOI: 10.1155/2020/5814296
|View full text |Cite
|
Sign up to set email alerts
|

Females with Type 2 Diabetes Mellitus Are Prone to Diabetic Retinopathy: A Twelve-Province Cross-Sectional Study in China

Abstract: Aims. To investigate the distribution of diabetic retinopathy (DR) by sex in patients with type 2 diabetes mellitus (T2DM) in a twelve-province cross-sectional study in China. Methods. Patients with T2DM, whose ages were ≥18 years, were recruited from 76 cities/counties in 12 provinces in mainland China between January 2015 and December 2018. All participants received a standardized interview, eye examinations, and digital fundus photography. The presence and severity of DR were diagnosed and classified by ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
(72 reference statements)
3
20
0
Order By: Relevance
“…Many studies showed that women were at greater risk of DR than men (Karwatowski et al, 2002). It was also estimated that females have a higher prevalence of DR than males in Japan and China (Kajiwara et al 2014; Li et al 2020). Moreover, pregnancy could accelerate the progression of retinopathy in women (Rahman et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that women were at greater risk of DR than men (Karwatowski et al, 2002). It was also estimated that females have a higher prevalence of DR than males in Japan and China (Kajiwara et al 2014; Li et al 2020). Moreover, pregnancy could accelerate the progression of retinopathy in women (Rahman et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 6 ] However, studies performed among older adults have suggested the two have a more complex relationship. [ 9 10 11 21 ] We found older age to be associated with a lower prevalence of DR in our study population. For the prevalence of a chronic disease to decrease at older age strata, it is probable that subjects with DR at younger ages are dying earlier.…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, Li et al . [ 10 ] performed a population-based study in Mainland China; their data suggested that females over the age of 60 have slightly increased odds of DR than their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the risk of DR in T2DM patients ≤ 60 years old was actually higher than that of patients > 60 years old. Research by Li et al 41 also showed that the risk for DR increased with age for people < 60 years old, while the prevalence of DR decreased with age for people > 60 years old, which may be due to the mortality rates of DM in populations > 60 years old being higher than those in younger patients; thus, the prevalence of DR was relatively low in the research subjects. In addition, people ≤ 60 years old paid more attention to their health and tended to have regular fundus examinations, and thus the higher detection rate of DR in the younger populations could be explained.…”
Section: Discussionmentioning
confidence: 78%